2017
DOI: 10.1111/weng.12238
|View full text |Cite
|
Sign up to set email alerts
|

English in Hong Kong higher education

Abstract: Research conducted in the late twentieth century pointed to a gulf in Hong Kong's universities between institutional medium‐of‐instruction policy, which stipulated the use of English, and lecturers’ classroom practices, which often involved the use of Cantonese to present and explain the content of English‐language textbooks and teaching materials. This article examines the findings of a study which sought to determine whether the policy‐practice divide had widened or narrowed in the past two decades under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…The observations made above offer a way of understanding how expectations to use a particular variety of English in Hong Kong are tied to ethnic identities. The ways in which our research participants use ethnicity to construct their English language identities demonstrate, as observed in previous scholarship (e.g., Evans, 2017;Joseph, 2000), that Hong Kong is a rich, yet perplexing, sociolinguistic space where multiple, and sometimes competing, voices co-exists. Such voices suggest that there is much to be gained from uncovering the cohabitation of different language ideologies, as discussed in Bakhtin's (1981) work on heteroglossia.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The observations made above offer a way of understanding how expectations to use a particular variety of English in Hong Kong are tied to ethnic identities. The ways in which our research participants use ethnicity to construct their English language identities demonstrate, as observed in previous scholarship (e.g., Evans, 2017;Joseph, 2000), that Hong Kong is a rich, yet perplexing, sociolinguistic space where multiple, and sometimes competing, voices co-exists. Such voices suggest that there is much to be gained from uncovering the cohabitation of different language ideologies, as discussed in Bakhtin's (1981) work on heteroglossia.…”
Section: Discussionsupporting
confidence: 72%
“…The efforts made by sociolinguists, in particular, contribute much to an understanding of what the Englishes of Hong Kong look like, how it is used, and the ways in which speakers position their linguistic identities in relation to English. Such work builds on the foundation of historical and cultural descriptions of the region offered in Bolton's earlier seminal research (e.g., Bolton, 2000), which continues today to provide a lens through which to describe how Englishes are used in Hong Kong (e.g., Evans, 2017) and the extent to which the language shapes the ideologies of its community members (e.g., Jenks & Lee, 2016). Yet despite past and ongoing efforts to better understand the social and ideological complexities of using English in the region, there continues to be a generalizing perception within and beyond scholarship that Hongkongers wish to mimic the speech patterns of monolingual speakers of English from the United States, United Kingdom, and other 'Inner Circle' regions.…”
Section: Introductionmentioning
confidence: 99%
“…For those whose first language is not English, this set of conditions might be harder to be fulfilled; the adoption of EMI education has therefore never been as smooth as expected. Many studies have identified the potential problems caused by language transitions from their first language (L1) to English [ 4 , 20 ]. By investigating students’ academic challenges, as well as the strategic tactics used by students for learning, this study aims to develop a better understanding of the effectiveness of EMI in higher education in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…Some schools and universities employ English as the medium of instruction (EMI), despite studies showing the benefits of mother tongue instruction and a strong correlation between academic achievements and learning in the mother tongue (Benson, 2004;Kosonen, 2005;Parba, 2018;Perez & Alieto, 2018). The use of EMI is often driven by socio-political, ideological, and economic reasons, including government policies, parent-driven demands, resourcing justifications, globalisation efforts, identity negotiations, and future study and career advances (Baldauf Jr. et al, 2011;Evans, 2017;Hu & McKay, 2012;Kosonen, 2005;Lin & Man, 2009;Parba, 2018;Rahman & Pandian, 2018). However, even in EMI institutions, where content subjects are taught in English, language use itself is not generally considered a part of learning content, and literacy in the disciplines is little developed.…”
Section: Julia Chen and Bruce Morrisonmentioning
confidence: 99%